2017
DOI: 10.3389/fpls.2017.00642
|View full text |Cite
|
Sign up to set email alerts
|

Silicon-Mediated Alleviation of Aluminum Toxicity by Modulation of Al/Si Uptake and Antioxidant Performance in Ryegrass Plants

Abstract: Silicon (Si) has been well documented to alleviate aluminum (Al) toxicity in vascular plants. However, the mechanisms underlying these responses remain poorly understood. Here, we assessed the effect of Si on the modulation of Si/Al uptake and the antioxidant performance of ryegrass plants hydroponically cultivated with Al (0 and 0.2 mM) in combination with Si (0, 0.5, and 2.0 mM). Exposure to Al significantly increased Al concentration, mainly in the roots, with a consequent reduction in root growth. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
51
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(59 citation statements)
references
References 112 publications
(193 reference statements)
5
51
0
3
Order By: Relevance
“…There are evidences have shown that Si can counteract the effects of excess of certain metals (e.g., Zn, Fe, Cu, Cd, Cr, Mn, As) [10,[38][39][40][41][42] by promoting: (i) cell wall-binding [10], (ii) modification of gene expression of PAL enzyme [38], (iii) phenotypical structural alterations that increase root length [39], (iv) changes to the number of leaves per plant and leaf area [40], and (v) changes to the thickness of epidermal layers of the leaf [41]. With respect to Al toxicity in particular, some studies have proposed that Si may reduce plant stress by promoting: (i) increases in the solution pH [43], (ii) the formation of aluminosilicates in the growth media and cell wall [43,65,66], (iii) the release of phenolic compounds by the root tips [47,60], (iv) increment of carotenoids and chlorophyll in leaves [67], and (v) stimulation of antioxidant enzyme activities and antioxidant compound production [23,44]. Nevertheless, there is still a controversial debate regarding the mechanisms implicated in the Si-mediated the attenuation of Al toxicity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There are evidences have shown that Si can counteract the effects of excess of certain metals (e.g., Zn, Fe, Cu, Cd, Cr, Mn, As) [10,[38][39][40][41][42] by promoting: (i) cell wall-binding [10], (ii) modification of gene expression of PAL enzyme [38], (iii) phenotypical structural alterations that increase root length [39], (iv) changes to the number of leaves per plant and leaf area [40], and (v) changes to the thickness of epidermal layers of the leaf [41]. With respect to Al toxicity in particular, some studies have proposed that Si may reduce plant stress by promoting: (i) increases in the solution pH [43], (ii) the formation of aluminosilicates in the growth media and cell wall [43,65,66], (iii) the release of phenolic compounds by the root tips [47,60], (iv) increment of carotenoids and chlorophyll in leaves [67], and (v) stimulation of antioxidant enzyme activities and antioxidant compound production [23,44]. Nevertheless, there is still a controversial debate regarding the mechanisms implicated in the Si-mediated the attenuation of Al toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, some studies have found an enhancement in the antioxidant system due to the action of Si under different stresses. Consequently, the increased production of flavonoids [47], activated antioxidant enzymes [17,23,44,46], decreased lipid peroxidation of the membranes [68], regulation of gene expression, and activation of key enzymes of the phenylpropanoid pathway [16,20,44,69] have all been identified.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although it is considered as a non-essential element in higher plants, this element is routinely supplied to several crops like rice and sugarcane to obtain high and sustainable crop yield [ 28 ]. In addition, it has also been observed that Si has a dynamic role in alleviating biotic and abiotic stress in plants such as pests and pathogens [ 29 , 30 ], metal toxicity [ 31 , 32 , 33 , 34 , 35 , 36 , 37 ], drought stress [ 38 , 39 ], mineral deficiency [ 40 ], salt stress [ 41 , 42 ], and UV-B stress [ 43 ]. The positive effects of Si have been largely observed in several crop plants such as wheat, barley, rice, cucumber, tomato, and soybean [ 44 , 45 , 46 , 47 ].…”
Section: Introductionmentioning
confidence: 99%